Enzymatic hydrolysis of delignified bagasse polysaccharides - Adsul, Mukund G.; Ghule, J. E.; Shaikh, H.; Singh, R.; Bastawade, Kulbhushan B.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2005)
Sugarcane bagasse, consisting of cellulose, xylan, and lignin, was chemically treated to generate bagasse samples with continuously decreasing content of lignin. These bagasse samples were hydrolyzed by cellulase and xylanase enzymes, produced earlier by Penicillium janthinellum NCIM 1171 in the same bagasse polysaccharides production medium. The hydrolysis was carried out by using different concentrations of the enzymes at two different temperatures, 30 and 50 degrees C, taking hydrolysis of Avicel as control. It was found that while the maximum hydrolysis for Avicel was 70% that of some of the bagasse polysaccharides was as high as 95%. The products of hydrolysis were glucose, xylose, and arabinose, as confirmed by high pressure ion chromatography (HPIC). It is interesting to note that arabinose, which constitutes about 10% of the weight of bagasse xylan, could also be released easily by the enzymes. Also, the initial rates of hydrolysis was found to be much higher for the bagasse polysaccharides, and in some cases about 90% of the hydrolysis occurred within 20 h. Amongst all bagasse samples, the sample with (Kappa no. 1.2, lignin content 0.18%) gave the highest degree of hydrolysis at 50 degrees C. Even the bagasse polysaccharide with Kappa no. 16.8 (lignin content 2.5%) underwent greater extent of hydrolysis than Avicel. Apparently, the delignified bagasse medium appears to be a facile medium for the combined hydrolytic action of the cellulase and xylanase enzymes. Considering that sugarcane bagasse is a waste biomass material available in abundance annually, this methodology can be used to value-add to this biomass to produce sugars, which can be fermented to produce biofuels like ethanol. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: bagasse polysaccharides; Cellulase; chemical treatment; Enzymatic hydrolysis; Penicillium janthinellum; Sugarcane bagasse; Xylanase

Purification and properties of a low molecular weight 1,4-beta-D-glucan glucohydrolase having one active site for carboxymethyl cellulose and xylan from an alkalothermophilic Thermomonospora sp - Jagtap, Sharmili; Rao, M (Biochemical and Biophysical Research Communications, 2005)
A low molecular weight 1,4-beta-D-glucan glucohydrolase from an extracellular culture filtrate of Thermomonospora sp. was purified to homogeneity. The molecular weight of the purified enzyme was 14.2 kDa by MALDI-TOF analysis and is in agreement with SDS-PAGE and gel filtration chromatography. The purified enzyme exhibited both endocarboxymethyl cellulase and endoxylanase activities. A kinetic method was employed to study the active site of the enzyme that hydrolyzes both carboxymethyl cellulose and xylan. The experimental data coincide well with the theoretical values calculated for the case of a single active site. Conformation and microenvironment at the active site was probed with fluorescent chemo-affinity labeling using o-phthalaidehyde as the chemical initiator. Formation of isoindole derivative resulted in complete inactivation of the enzyme to hydrolyze both xylan and CMC as judged by fluorescence studies corroborating a single active site for the hydrolysis of xylan and CMC. (C) 2005 Elsevier Inc. All rights reserved.
Keywords: Cellulase; CMC; OPTA; single active site; Thermomonospora sp.; xylan; Xylanase

Biochemical characterization of a novel beta-1-3, 1-4 glucan 4-glucanohydrolase from thermomonospora sp having a single active site for lichenan and xylan - Anish, Ramakrishnan; Rao, Mala (Biochimie, 2007)
A bifunctional high molecular weight (Mr, 64,500 Da) beta-1-3, 1-4 glucan 4-glucanohydrolase was purified to homogeneity from Thermomonospora sp., exhibiting activity towards lichenan and xylan. A kinetic method was used to analyze the active site that hydrolyzes lichenan and xylan. The experimental data was in agreement with the theoretical values calculated for a single active site. Probing the conformation and microenvironment at active site of the enzyme by fluorescent chemo-affinity label, OPTA resulted in the formation of an isoindole derivative with complete inactivation of the enzyme to hydrolyse both lichenan and xylan confirmed the results of kinetic method. OPTA forms an isoindole derivative by cross-linking the proximal thiol and amino groups. The modification of cysteine and lysine residues by DTNB and TNBS respectively abolished the ability of the enzyme to form an isoindole derivative with OPTA, indicating the participation of cysteine and lysine in the formation of isoindole complex. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: 1-4 glucan 4-glucanohydrolase; beta-1-3; bifunctional; O-phthaialdehyde; single active site; Thermomonospora sp.; Xylanase

Encapsulation of endoglucanase using a biopolymer Gum arabic for its controlled release - Ramakrishnan, Anish; Pandit, Nilesh; Badgujar, Mahesh; Bhaskar, C.; Rao, Mala (Bioresource Technology, 2007)
{Gum Arabic, a biodegradable natural polymer was used as a matrix to encapsulate endoglucanase from Thermomonospora sp. The modified enzyme retained complete biocatalytic activity and exhibited a shift in the optimum temperature [
Keywords: Enzyme catalysis; OPTA; Thermomonospora sp.; Xylanase

Formal synthesis of herbarumin III - Gupta, Priti; Kumar, Pradeep (Tetrahedron-Asymmetry, 2007)
An enantioselective synthesis of herbarumin III is described employing Jacobsen's hydrolytic kinetic resolution and Sharpless asymmetric dihydroxylation as the key steps. (c) 2007 Published by Elsevier Ltd.
Keywords: carboxymethyl-cellulase; F. moniliforme; pectate lyase; plant pathogenesis; polygalacturonase; Xylanase

Glycine-assisted enhancement of 1,4-beta-D-xylan xylanohydrolase activity at alkaline pH with a pH optimum shift - Vathipadiekal, Vinod; Verma, Anamika; Rao, Mala (Biological Chemistry, 2007)
This is the first report describing the enhancement of xylanase activity by the neutral amino acid glycine. Xylanase activity is increased seven-fold at alkaline pH in the presence of glycine and its pH optimum is shifted from pH 7 to 8 without using any protein engineering techniques. Analysis of the steady-state kinetics revealed that glycine in the reaction mixture increases the K-m and k(cat) values of the enzyme. Chemoaffinity labeling and studies using glycine esters indicate an involvement of the carboxylate ion of glycine in enhancing xylanase catalytic activity. A novel possible mechanism for the glycine-assisted catalytic action of xylanase is proposed.
Keywords: Enzyme catalysis; OPTA; Thermomonospora sp.; Xylanase

Optimal xylanase production using Penicilium janthinellum NCIM 1169: a model based approach - Meshram, Mukesh; Kulkarni, Abhijit; Jayaraman, Valadi K.; Kulkarni, B. D.; Lele, S. S. (Biochemical Engineering Journal, 2008)
Xylanases are an industrially important class of hydrolytic enzymes that degrade xylans. Production of xylanase from a fungal culture by submerged fermentation and optimization of the operating conditions for maximum activity are the two aims of the present study. Penicillium janthinellum NCIM 1169 with Mandels-Weber medium, sugarcane bagassse (40#) as a carbon source and beef extract as a nitrogen source were used in the experiments. We did 41 experiments to see the effect of variations in carbon, nitrogen source, pH, and inoculum on xylanase activity. This data was then used to build an input/output model using multiple linear regression, back propagation neural network and lazy learning algorithm. It was found that lazy learning model correlated well in mapping input/output data. This model was then utilized as an objective function in genetic algorithm to find the optimal combination of the operating conditions to get the maximum xylanase activity. It was observed that with carbon source, 1.63%, nitrogen source, 0.16%, pH, 4.1, and inoculum, 5.5%, maximum xylanase activity of 28.98 +/- 1.73 U/ml was achieved. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Artificial intelligence; Enzyme activity; Fermentation; Modeling; Optimization; Xylanase

Production of single cell protein, essential amino acids, and xylanase by penicillium janthinellum - Rao, Mala; Varma, Anjanikumar; Deshmukh, Sumedha S. (Bioresources, 2010)
Microbial biomass having 46% crude protein content and enriched with essential amino acids as well as extracellular xylanase activity (100-150 IU/ml) was produced by an efficient fungal strain, Penicillium janthinellum (NCIM St-F-3b). Optimization studies for maximum xylanase and biomass production showed that the fungus required a simple medium containing bagasse hemicellulose as carbon source and ammonium sulphate as the nitrogen source. Therefore bagasse, which is a waste product of the sugar industry, can be efficiently used in microbioal biomass protein preparation for animal feed.
Keywords: Bagasse hydrolysate; Crude protein; Microbial biomass production; Penicillium janthinellum; Xylanase

Bioprocess optimization of penicillium funiculosum NCIM 1228 for improved production and hydrolytic efficiency of cellulases on sugarcane bagasse - Chavan, Sambhaji B.; Shete, Ashvini M.; Dharne, Mahesh S. (Sugar Tech, 2024)
The cellulase enzyme is currently the world's third largest commercial enzyme. Because of its requirement in various industries like textiles, food, waste management, pharmaceuticals, agriculture, pulp paper, biofuels, and others, its demand curve has increased sharply. The response surface methodology (RSM) approach was employed to optimize media components and process parameters in the current investigation, which successfully increased the cellulase production from Penicillium funiculosum NCIM 1228. Statistical optimization for the hyperproduction of cellulases was conducted using RSM. The Plackett-Burman design (PBD) approach was used to investigate the critical factors of the cellulase production medium. Subsequently, the Box-Behnken design (BBD) method was used to statistically estimate optimum values and conditions that substantially impacted cellulase production. The estimated optimal combinations of parameters for cellulase production were urea (0.2%), CaCl2 (0.2%), MgSO4 (0.05%), peptone (1.5%), microcrystalline cellulose (5.0%), wheat bran (2.5%), corn steep liquor (CSL) (2.5%), KH2PO4 (0.15%), inoculum (10.65%), agitation (157 rpm), pH (5.88), and temperature (29.84 C-degrees). Conclusively, experimental validation under optimal conditions detected an increased production of 3.82- and 3.61-fold in filter paper assay (FPase) and beta-glucosidase, respectively. Additionally, 1.66- and 1.57-fold enhancement in FPase and beta-glucosidase specific activity was observed where an xylanase activity was enhanced by 3.29-fold. Furthermore, the enzyme showed 51.30 per cent hydrolysis efficiency on sugarcane bagasse lignocellulosic biomass (LCB), at a dose of 7 FPase units per g of cellulose. P. funiculosum NCIM 1228 offers the benefit of producing cellulase with an entire cellulolytic system of enzymes that can be synthesized extracellularly, thus acting as a promising biocatalyst for biofuel industries.
Keywords: Cellulase; Lignocellulosic biomass; Penicillium funiculosum; Response surface methodology; Submerged fermentation; Xylanase